Major Events in the Recent Past in Assembly Speeches and the Authenticity of [Andocides] On the Peace - Harris, Edward (Tekmeria, 2021)
This paper begins by demonstrating that speakers in the Assembly did not misrepresent major events in recent history. An examination of Demosthenes’ speeches to the Assembly shows that his statements about recent events are accurate but are usually brief. This is true for speeches to the Assembly found in Thucydides and Xennophon. The main part of the essay shows that the speech On the Peace attributed to Andocides makes major mistakes about recent events (such as the walls and fleet of Athens, peace between the Boeotians and the Spartans, Athenian control over Euboea, peace with Persia, etc.). The speech also does not conform to the rhetorical conventions of the Assembly (naming one’s ancestors, giving lengthy accounts of past events), contains statements about presbeis autokratores which are inconsistent with the evidence for this institution in Classical Greece and uses the term spondai in a way unparalleled in classical sources. All this evidence shows that the speech is not a genuine work of Andocides but a forgery composed in the Hellenistic or Roman period.